Population Health Tracking System: Analyzing Health Data for Effective Healthcare Planning - Aneesh Bose; Deblina Pal; Radhakrishna Jana (International Journal of Computer Sciences and Engineering, 2023)
The primary objective of this undertaking is to acquire a comprehensive understanding of the health status of a designated region, be it a district, state, or even an entire country. The central methodology employed in this project involves the meticulous accumulation of significant health-related data, which is subsequently translated into visually informative displays. To facilitate this, an extensive survey was meticulously conducted among the populace of Assam, constituting a pivotal phase in the data acquisition process. The resultant data corpus was then meticulously categorized according to their respective geographic subdivisions. Within the realm of this analysis, particular focus was directed towards three prevalent ailments: asthma, chronic illnesses, and arthritis. These health conditions were chosen as the focal points due to their widespread impact on the populace. To effectively convey the prevalence of each malady, a standardized metric was employed wherein the frequency of cases was represented relative to a population of one lakh. The utilization of graphical representations serves as a potent tool in conveying intricate health-related insights to a broader audience. By visually portraying the prevalence of key diseases across various districts, a clearer understanding of the health landscape emerges. This comprehensive approach to data collec- tion and visualization is pivotal in facilitating informed decision- making processes for healthcare providers, policymakers, and stakeholders alike.